POSISI PEKERJA OUTSOURCING DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Wahyuni, Dinar (Jurnal Aspirasi, 2011)
Outsourcing is legitimate after Act No. 13 of 2003 regarding employment was passed. This paper tries to analyze the position of outsourced workers in the act from three dimension i.e. worker relations, worker unions, industrial conflict and its resolution. From the worker relations dimension, workers’ status is unclear because the outsourcing agreement made was between the employee and the outsourcing companies. There has been inconsistencies in application of working agreement, and this will reduce workers’ rights. From the trade unions dimensions, the practice of outsourcing will further minimize the function and role of unions within the company. From the industrial conflict dimensions and its resolution, if a conflict occur, the authorities who resolve the dispute is the outsourcing company. It happens because the agreement made is between the worker and the outsourcing company.